2016
DOI: 10.1080/02713683.2016.1238943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molsidomine on Retinopathy and Oxidative Stress Induced by Radiotheraphy in Rat Eyes

Abstract: We suggest that MOL is a powerful antioxidant and free radical scavenger that prevents the rat eyes from radiation-induced retinopathy and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Indeed, studies have shown that oxidative stress in the degenerating retinas is considerably higher than that of normal retinas. Apart from retinal degeneration, oxidative damage is also a key pathology of many other diseases, such as age-related macular degeneration, glaucoma, diabetic retinopathy (31), retinopathy of prematurity (30), dry eye syndrome (32), keratitis (33), and retinopathy after radiotherapy (34). Different antioxidants have been used in the clinic to treat patients with degenerative diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that oxidative stress in the degenerating retinas is considerably higher than that of normal retinas. Apart from retinal degeneration, oxidative damage is also a key pathology of many other diseases, such as age-related macular degeneration, glaucoma, diabetic retinopathy (31), retinopathy of prematurity (30), dry eye syndrome (32), keratitis (33), and retinopathy after radiotherapy (34). Different antioxidants have been used in the clinic to treat patients with degenerative diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…or decreased antioxidant capacity (caused by malnutrition or aging, etc.) leads to oxidant/antioxidant imbalances in vivo [36][37][38][39]. Oxidative stress generated by oxidant/antioxidant imbalances results in cell damage and dysfunction.…”
Section: Molecular Aspects Of Oxidative Stress-induced Cell Damagementioning
confidence: 99%
“…Intraocular surgery includes cataract surgery [103], beta radiation therapy [104], and laser posterior capsulotomy [105]. It has been reported that intraocular surgery causes a significant decrease in ECD, which is possibly related to the oxidative stress that surgery causes [37][38][39]. Decreased ECD is a significant cause of the loss of function in transplanted corneas, and ECD can predict the success of corneal transplantations [106][107][108].…”
Section: Others (Oxidative Stress-related Surgical Complications)mentioning
confidence: 99%
“…It can be used to treat the eye tissue damage caused due to ionizing radiation. 13 , 14 , 15 Until now, there are no data of molsidomine acting against diabetic peripheral neuropathy. Therefore, the present study was designed to evaluate the protective effect of molsidomine against diabetic peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%